2020
DOI: 10.1021/jacs.9b12343
|View full text |Cite
|
Sign up to set email alerts
|

Base-Promoted C–C Bond Activation Enables Radical Allylation with Homoallylic Alcohols

Abstract: The C α −C β bond in homoallylic alcohols can be activated under basic conditions, qualifying these nonstrained acyclic systems as radical allylation reagents. This reactivity is exemplified by photoinitiated (with visible light and/or blue LEDs) allylation of perfluoroalkyl and alkyl radicals generated from perfluoroalkyl iodides and alkylpyridinium salts, respectively, with homoallylic alcohols. Cradical addition to the double bond of the title reagents and subsequent base-promoted homolytic C α −C β cleavag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 75 publications
0
25
0
Order By: Relevance
“…While the majority of reaction conditions did not call for strongly acidic or oxidizing reagents, the reaction temperature often surpassed 100 °C. One possible direction could be emerging radical-driven processes that allow for C–C bond cleavages under mild conditions. ,, Moreover, using first-row transition metals might allow the exploitation of different reaction pathways compared to precious Pd and Rh catalysts that were predominantly used in the field. Three examples using Mn, Co, and Ni were discussed herein.…”
Section: Discussionmentioning
confidence: 99%
“…While the majority of reaction conditions did not call for strongly acidic or oxidizing reagents, the reaction temperature often surpassed 100 °C. One possible direction could be emerging radical-driven processes that allow for C–C bond cleavages under mild conditions. ,, Moreover, using first-row transition metals might allow the exploitation of different reaction pathways compared to precious Pd and Rh catalysts that were predominantly used in the field. Three examples using Mn, Co, and Ni were discussed herein.…”
Section: Discussionmentioning
confidence: 99%
“…45 In 2020, Studer and co-workers applied their approach to the visible light-initiated allylation of radicals using homoallylic alcohols (Scheme 25). 46 In this variant, perfluoroalkyl radicals and simple alkyl radicals -formed from pyridinium salts 168were generated and engaged in radical additions to homoallylic alcohols 166 to yield allylated products 169 after base-promoted homolytic cleavage of the C a -C b bond. This SET chain process is sustained by the reduction of 167 or 168 by the resultant ketyl radicals 175 or 176.…”
Section: Intermolecular Couplingsmentioning
confidence: 99%
“…Scheme 25 Visible light-initiated radical allylation using homoallylic alcohols and base (Studer, 2020).…”
Section: Electrochemically Generated Ketyl Radicalsmentioning
confidence: 99%
“…In the photoredox cycle, [ Except allyl sulfones, recently Studer and coworkers demonstrated that homoallylic alcohols could be used as the allylation reagents (Scheme 3). [17] In this work, a series of primary benzylic and secondary Katritzky salts were successfully allylated with homoallylic alcohols by employing i-Pr 2 NEt as the base in DMA under blue LEDs irradiation. According to computations, the hydrogen bond between homoallylic alcohols and the base could promote CÀ C bond homolysis, and the ketyl radical A was acted as the reductant to make the alkyl radical formation.…”
Section: Radical Addition To Alkenesmentioning
confidence: 99%